A secure encryption scheme based on certificateless proxy signature. (2018) - Sudharani, K.; Sakthivel, P.N.K.
Certificateless public key cryptography (CL-PKC) scheme is introduced for solving the key escrow problems in the identity-based cryptography and eliminate the use of security certificates. By introducing the proxy signature concept in the certificateless cryptography scheme, this certificateless proxy signature (CLPS) scheme has attracted the attention of more researchers. However, this scheme suffers due to the security issues and fails to achieve the unforgeability against the attacks. To overcome the security issues in the existing cryptographic scheme, this paper proposes an encryption scheme based on the certificateless proxy signature for sharing the sensitive data in the public cloud in a secure manner. The proposed scheme is proven to be unforgeable against the message attacks. When compared with the existing CLPS scheme without random oracles, the proposed scheme offers better data security while ensuring better data sharing performance. From the experimental results, it was noticed that the proposed scheme requires minimum encryption and decryption time than that of existing scheme.